The Role of Psychoeducation Using Positive Thinking Techniques in Enhancing the Psychological Well–Being of Adolescents in Special Child Development Institutions (LPKA) - Pulungan, Syakirah Tazkiyah; Darussalim, Darussalim; Hasibuan, Rini Syahrayni (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
Research on the psychological well-being of children in conflict with the law remains limited, particularly within juvenile correctional settings that emphasize rehabilitation rather than punishment. Therefore, this study aimed to examine the effectiveness of psychoeducation using positive thinking training techniques in enhancing the psychological well-being of adolescents residing in a Special Child Development Institution (LPKA). This study employed a quasi-experimental pre-test–post-test control-group design involving 20 adolescents, consisting of 10 participants in the experimental group and 10 participants in the control group. The experimental group received psychoeducational intervention in the form of positive thinking training, while the control group did not receive any treatment. Psychological well-being was measured using the Happiness Psychological Scale developed by Anggoro and Widhiarso (2010). Data were analyzed using the Mann–Whitney U test and the Wilcoxon signed-rank test. The results of the Mann–Whitney U test indicated a significant difference in psychological well-being between the experimental and control groups (Z = −2.881, p = .004, p < .05), with the experimental group demonstrating higher psychological well-being scores (M = 14.30) than the control group (M = 6.70). In addition, the Wilcoxon signed-rank test revealed a significant increase in psychological well-being within the experimental group between the pre-test and post-test conditions (Z = −1.955, p = .037, p < .05). These findings provide empirical evidence that psychoeducation delivered through positive thinking training effectively enhances adolescents’ psychological well-being in juvenile correctional institutions. The novelty of this study lies in its focus on children in conflict with the law and its examination of psychological well-being as a multidimensional construct within an institutional rehabilitation context, an area that has received limited empirical attention in prior research. The results highlight the potential of psychoeducational interventions as evidence-based strategies to support psychological development and rehabilitation among institutionalized youth.